Agronomic properties of Aleman grass, Para grass and Setaria grass mixture and its palatability in sheep - Mohd Nor, Muhamad Hanif (2016)
A study was conducted to evaluate the agronomic properties of Aleman grass (Echinochloa polystachya), Para grass (Brachiaria mutica) and Setaria grass (Setaria splendida) mixture and its palatability in sheep. The first objective of this study was to evaluate the agronomic properties in mix planting of Aleman grass, Para grass, and Setaria grass that includes the botanical composition, tiller count, grass height, and leaf to stem ratio. The second objective of this study was to evaluate the palatability of the mixture of Aleman grass, Para grass and Setaria grass by sheep. The grass were planted in single, two grass mixture and three grass mixture at the Field 2, Department of Animal Science University Putra Malaysia. The grass were planted for 2 months in a randomly complete block design (RCBD) and was cut about 15 cm for each grass and the data was collected every week. Botanical composition and grass tiller count showed no different among the grass planted as single grass to the planted two and three grass species. There was a significant difference (P>0.05) in grass height that decreased in two and three grass mixture. The study on palatability was conducted using single bowl and double bowl method. There were significant differences (P<0.05) in both tests that the single grass was more palatable than mixture of two and three grasses. The mixture of three grass takes more time for the sheep to finish the grass compared to the mixture of two and single grass species. In conclusion, this result showed that different mixture of planting and feeding to the animal have an effect on agronomic properties and its palatability in sheep.